PENGARUH MODEL TALKING STICK TERHADAP HASIL BELAJAR IPS SISWA KELAS III - Likus, Likus; Marli, Suhardi; Utami, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe influence of Talking Stick on the results of the study in Social Subject in the third grade students The purpose of this study is to describe how effective the use of stick talking to the results of learning in social class. This research is an experimental research in the form of experimental non experimental experimental group design. The sample of this research is third grade students consisting of 60 students and divided by 30 control class students and 30 students of experiment class. Data collection techniques used are measurement techniques and data collection tool test. Based on statistical calculation the mean of post test of control class is 66,1 and experiment class is 70,7. Result of hypothesis used t test with t count = 1,7168 and ttabel = 1,6723. Then Ha accepted. From these results, the efeect size is 0.45 and categorized as moderate. Based on the above findings, it can be concluded that there is influence Talking Stick on the results of the Study on Social Subjects third class SDN 34 Pontianak City with category medium.Â Â Keywords: Influence, Model Talking Stick, Learning Outcomes